ANALISIS FAKTOR PENYEBAB KLAIM PENDING PASIEN RAWAT INAP BPJS KESEHATAN DI RUMAH SAKIT TENTARA DR. SOEPRAOEN MALANG TAHUN 2023 - Zein, Eiska Rohmania (Politeknik Kesehatan Kemenkes Malang, 2023)
The process of submitting a claim from the hospital to BPJS Kesehatan if incompleteness is found in the verification process will result in the return of the file by BPJS Kesehatan, which can result in a pending claim. There are several cases of pending claims at Dr. Army Hospital. Soepraoen. The purpose of this study is to analyze the factors that cause Pending Claims for BPJS Kesehatan Inpatient Patients at Dr. Army Hospital. Soepraoen Malang in 2023 with a descriptive quantitative research method. The sample of this research is 60 pending claim files in February-March. The results of this study obtained pending claims based on coding factors as many as 26 documents or 43% inappropriate diagnosis codes, based on medical factors as many as 31 documents or 52% incomplete, based on administration factors as many as 3 documents or 5% inappropriate.